Prevalence of burnout and Its associated factors among medical students in a public university in Selangor, Malaysia: a cross-sectional study - Thew, Hui Zhu; Ching, Siew Mooi; Sallahuddin, Nurin Amalina; Nooralirakiz, Puteri Nur Dayana; David, Thessa Sharmila; Zaidi, Imran Kamal Hafiz; Devaraj, Navin Kumar; Lee, Kai Wei; Ali, Hanifatiyah; Abdul Manap, Abdul Hadi; Mohamad, Fadzilah; Suppiah, Subapriya; et al. (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2023)
Introduction: Burnout is a growing trend among medical students worldwide. The aim of this study was to determine the prevalence and factors associated with burnout among medical students at a public university in Malaysia. Methods: A cross-sectional study was conducted among 1st through 5th year medical students at a public university using a simple random sampling method in recruiting participants. In this study, The Maslach Burnout Inventory-General Survey for Student (MBI-SS) was used and burnout is defined as severely emotionally exhausted and severely depersonalised. Results: A total of 328 medical students were recruited with a with response rate of 88.6%. The burnout prevalence was 10.1%. Based on multivariate logistic regression, presence of smartphone addiction with adjusted (odds ratio (OR) 7.37, 95% confidence interval (CI) = 1.67, 32.49), course choice not based on personal interest or due to family pressure (OR 2.72, 95% CI = 1.08, 6.85) and the presence of family relationship problems (OR = 3.58, 95% CI = 1.27, 10.04) are more likely to be associated with burnout among the medical students. Conclusion: Our study has shown that every tenth medical students suffers from burnout. Medical students who are addicted to smartphone, have chosen medical course against individual interest or because of family pressure and have family relationship problems are at risk of getting burnout. Intervention is required to address this issue for the future well-being of medical students.